"The system has to be health literate, too" - perspectives among healthcare professionals on health literacy in transcultural treatment settings - Annika Baumeister; Digo Chakraverty; Angela Aldin; Ümran Sema Seven; Nicole Skoetz; Elke Kalbe; Christiane Woopen (BMC, 2021)
Abstract Background Effective communication is a central aspect of organizational health literacy. Healthcare professionals are expected to ensure an effective and satisfactory flow of information and to support their patients in accessing, understanding, appraising, and applying health information. This qualitative study aimed to examine the health literacy-related challenges, needs, and applied solutions of healthcare professionals when engaging with persons with a migrant background. Based on the integrated model of health literacy (Sørensen et al., BMC Public Health 12:80, 2012), we focused on environmental, personal, and situational factors that shape health literacy in transcultural treatment settings. Methods We conducted five focus group discussions with healthcare professionals (N = 31) who are in regular contact with persons with a migrant background. Discussions were transcribed verbatim and analyzed using qualitative content analysis by applying a deductive-inductive categorization procedure. Deductive categories were derived from the integrated model of health literacy. Results Challenges included a mismatch in the provision and use of health services. Participants regarded easily accessible services and outreach counselling as helpful solutions. Further challenges were the migrant patients' distrust in healthcare professionals and the German healthcare system, the participants' uncertainty in dealing with patients' expectations and needs, and the patients' non-compliance with appointments. Environmental factors included systemic lack of time and economic pressure. Both were reported as impeding the flow of information in all treatment settings. Participants with a migrant background themselves (n = 16) regarded this personal factor as an opportunity that increased patients' trust in them. They also reported challenges such as high levels of responsibility felt when ad hoc interpreting for colleagues. Conclusions Known issues observed in the delivery of healthcare for the majority population (i.e., systemic lack of time, economic pressure) appear to be intensified in the context of migration. An increasingly diverse patient clientele indicates a growing need for culture-sensitive, health-literate healthcare organizations. A corresponding diversity of the health workforce is desirable and should be strengthened by national finance and educational programs. Healthcare professionals who interpret for colleagues should be given the necessary time. Further studies are needed to develop appropriate interventions for improving health literacy at individual and organizational levels. Funding for interpreting services should be expanded.